Blind separation of asymmetric PCMA signal based on soft information joint correction - Qiang HUANG; Hua PENG; Tian-yun LI; Ke-xian GONG (Tongxin xuebao)
On the basis of a blind separation structure with low complexity,an efficient blind separation algorithm based on soft information joint correction was proposed for asymmetric PCMA to improve the demodulation performance of strong and weak signals.By utilizing the demodulation mutual influence between the strong and weak signals,this algorithm tried to correct the receiving symbols of strong signal with high error probability.Comparing the symbol constellation quality (soft information) of signals before and after correction,it can be decided whether the hard decision values of strong and weak signals need to be modified,which efficiently reduce the demodulation error rate of strong and weak signals.The simulation results show that,the demodulation error rate of strong and weak signals can be reduced by nearly two orders of magnitude after joint correction especially when the signal to noise ratio of strong signal is higher than 17 dB,and the computational complexity of this algorithm is lower than that of the conventional reconstruction cancellation algorithm.